High-speed FSO-5G wireless communication system with enhanced loss compensation using high-power EDFA - Stotaw Talbachew Hayle; Hua-Yi Hsu; Chia-Peng Wang; Hai-Han Lu; Jia-Ming Lu; Wei-Wen Hsu; Yu-Chen Chung; Yu-Yao Bai; Kelper Okram (Scientific Reports)
Abstract In this paper, we demonstrated a novel bidirectional high-speed transmission system integrating a free-space optical (FSO) communication with a 5G wireless link, utilizing a high-power erbium-doped fibre amplifier (EDFA) for enhanced loss compensation. The system supports downlink rates of 1-Gb/s/4.5-GHz and 10-Gb/s at 24-GHz and 39-GHz, and an uplink rate of 10-Gb/s/28-GHz. The high-power EDFA boosts signal strength, facilitating reliable long-distance transmission through the FSO transmission link while compensating for losses and reducing bit error rates (BER) and error vector magnitude (EVM). Fibre Bragg grating sensors are employed as wavelength selectors for both downlink and uplink, offering a simpler, cost-effective solution compared to previously utilized reflective semiconductor optical amplifiers and multiple laser sources. The system successfully transmits 16-quadrature amplitude modulation orthogonal frequency division multiplexing signals across various carrier frequencies, achieving total data rates of 21-Gb/s for downlink and 30-Gb/s for uplink across a 1.6-km FSO transmission link integrated with 10/15-m 5G links. Performance metrics, including low EVM and BER, and well-defined constellation patterns, indicate the reliability and effectiveness of the system. This bidirectional FSO-5G wireless communication system offers a high-speed and cost-effective solution for extending 5G coverage in both densely and sparsely populated areas.